Adaptability versus certainty in a carbon emissions reduction regime: An assessment of the EU's 2030 Climate and Energy Policy Framework. Issue 2 (4th July 2020) - Torney, Diarmuid; O'Gorman, Roderic
Abstract: The Paris Agreement moves away from top‐down agreed national targets towards a bottom‐up system in which each party submits regular nationally determined contributions (NDCs). The Agreement outlines a highly adaptable process in which, every five years, parties are required to update their NDCs, which must represent a progression on their existing contribution. This article analyses the extent to which the European Union's 2030 Climate and Energy Policy Framework has created an adaptable structure that reflects the Paris Agreement's ratchet mechanism. The article contrasts this approach with the carbon budget process adopted under the United Kingdom's Climate Change Act. The article assesses the respective advantages and disadvantages of creating a system where targets are easily increased on a medium‐term basis allowing responsiveness to changed circumstances such as scientific data indicating the need for more rapid emission reductions, versus a stable system that provides greater certainty for economic actors.